2000
DOI: 10.1523/jneurosci.20-18-06989.2000
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Phosphorylation of NMDA Receptor 1 Subunits in Spinal Cord Dorsal Horn and Spinothalamic Tract Neurons after Intradermal Injection of Capsaicin in Rats

Abstract: The functional enhancement of NMDA receptors after peripheral tissue injury is proposed to contribute to the sensitization of spinothalamic tract (STT) cells and hyperalgesia. Protein phosphorylation is a major mechanism for the regulation of NMDA receptor function. In this study, Western blots, immunofluorescence double labeling, and the retrograde tracing method were used to examine whether phosphorylation of NMDA receptor 1 (NR1) subunits increases in spinal cord tissue and spinal dorsal horn neurons, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
89
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 71 publications
14
89
2
1
Order By: Relevance
“…It is well known that p-NR1 modulates NMDAR activity and facilitates nociceptive input transmission in inflammatory pain models [3][4][5]. This suggests that inflammation-enhanced IL-17A might facilitate pain through NR1 phosphorylation, and EA might decrease spinal …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that p-NR1 modulates NMDAR activity and facilitates nociceptive input transmission in inflammatory pain models [3][4][5]. This suggests that inflammation-enhanced IL-17A might facilitate pain through NR1 phosphorylation, and EA might decrease spinal …”
Section: Discussionmentioning
confidence: 99%
“…These cells produces a number of algesic substances such as the proinflammatory cytokines interleukin 1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), and IL-6 to promote spinal transmission and processing of noxious signals [1,2]. It is reported that IL-1β is up-regulated in spinal astrocytes to increase NMDA NR1 phosphorylation, an essential subunit of the N-methyl Daspartate receptor (NMDAR), which in turn promote pain in an inflammatory pain rat model [3][4][5][6] . IL-17A, recently found in astrocytes of patients with multiple sclerosis [7], increase in concentration in the spinal cord of rats with nerve injury [8].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral tissue injury dramatically enhances the function of spinal NMDA receptor that is involved in the initiation and maintenance of central sensitization, a persistent increase in the excitability of nociceptive neurons [2,3,28,29] . The hyperfunction of the NMDA receptor could result from phosphorylation, upregulation, or a combination of both [30,31] . Our western blot analysis indicated that the NMDA receptor NR1 subunit was phosphorylated but not upregulated in the ARC, and this effect was enhanced in inflamed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of NR1 has been shown to induce NMDA receptor trafficking from storage sites in the endoplasmic reticulum to the synaptic plasma membrane, leading to a hyperactivation state of NMDA receptor in nociceptive transmis sion [35,36] . Furthermore, NR1 phosphorylation has been correlated with hyperalgesia and allodynia, which are characteristic behavioral manifestations of central sensitization [31,37] . Previous investigations have demonstrated that the blockage of NR1 phosphorylation could reverse allodynia [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, involvement of 5␣-DHP and 3␣,5␣-THP biosynthetic pathways in the regulation of nociception needs to be considered in regard to various neurobiological mechanisms occurring in both acute and chronic phases of pain, even though in vivo studies have shown that 3␣,5␣-THP and its synthetic analogs induce antinociceptive effects in rats and humans (40-43). It is also important to recall that rNK1-mediated hyperalgesia seems to be an extremely complex mechanism involving the release of prostanoids (44,45) and glutamate (46,47), and the phosphorylation of NMDA receptor through a protein kinase C transduction process (48,49). Therefore, we suggest here an hypothetical model to recapitulate and clarify neurochemical events that may occur in spinal Values are the mean Ϯ SEM of four independent experiments.…”
Section: Discussionmentioning
confidence: 97%